Metagenomic Analysis Reveals Changes in Bacterial Communities and Antibiotic Resistance Genes in an Eye Specialty Hospital and a General Hospital Before and After Wastewater Treatment - Ma, Xueli; Dong, Xu; Cai, Jiabei; Fu, Chunyan; Yang, Jing; Liu, Yuan; Zhang, Yan; Wan, Tian; Lin, Shudan; Lou, Yongliang; Zheng, Meiqin (Frontiers in Microbiology, 2022)
The spread of antibiotic resistant bacteria (ARB) and antibiotic resistance genes (ARGs) in hospital wastewater poses a great threat to public health, and wastewater treatment plants (WWTPs) play an important role in reducing the levels of ARB and ARGs. In this study, high-throughput metagenomic sequencing was used to analyze the bacterial community composition and ARGs in two hospitals exposed to different antibiotic use conditions (an eye specialty hospital and a general hospital) before and after wastewater treatment. The results showed that there were various potential pathogenic bacteria in the hospital wastewater, and the abundance and diversity of the influent ARGs in the general hospital were higher than those in the eye hospital. The influent of the eye hospital was mainly composed of Thauera and Pseudomonas, and sul1 (sulfonamide) was the most abundant ARG. The influent of the general hospital contained mainly Aeromonas and Acinetobacter, and tet39 (tetracycline) was the most abundant ARG. Furthermore, co-occurrence network analysis showed that the main bacteria carrying ARGs in hospital wastewater varied with hospital type; the same bacteria in wastewater from different hospitals could carry different ARGs, and the same ARG could also be carried by different bacteria. The changes in the bacterial community and ARG abundance in the effluent from the two hospitals showed that the activated sludge treatment and the direct chlorination disinfection can effectively remove some bacteria and ARGs in wastewater but have limitations. The species diversity increased significantly after the activated sludge treatment, while the direct chlorination disinfection did not increase the diversity. The activated sludge treatment has a better effect on the elimination of ARGs than the direct chlorination disinfection. In summary, we investigated the differences in bacterial communities and ARGs in wastewater from two hospitals exposed to different antibiotic usage conditions, evaluated the effects of different wastewater treatment methods on the bacterial communities and ARGs in hospital wastewater, and recommended appropriate methods for certain clinical environments.